Експериментальне обґрунтування методики розрахунку нормованих параметрів заземлювального пристрою на основі тришарової моделі ґрунту - Коліушко, Д.Г.; Руденко, С.С. (Електротехніка і електромеханіка, 2018)
Проведено аналіз можливості застосування розробленої методики визначення нормованих параметрів заземлювального пристрою, розташованого в тришаровому ґрунті, шляхом порівняння результатів експериментальних вимірів з розрахунковими значеннями для діючих високовольтних підстанцій України. Показано, що середня похибка розрахунку значення опору заземлювального пристрою знизилася з 18 % для двошарової моделі ґрунту до менше 10 % для тришарової моделі. Порівняння розрахункових та експериментально визначених значень напруги дотику показало високу ступінь їх співпадіння Выполнен анализ возможности применения разработанной методики определения нормируемых параметров заземляющего устройства, расположенного в трехслойном грунте, путем сравнения результатов экспериментальных измерений с расчетными значениями для действующих высоковольтных подстанций Украины. Показано, что средняя погрешность определения значения сопротивления заземляющего устройства снизилась с 18 % для двухслойной модели до менее 10 % для трехслойной модели. Сравнение расчетных и экспериментально определенных значений напряжения прикосновения показало высокую степень их совпадения Purpose. Experimental substantiation of the possibility of using the calculation procedure of normalized parameters grounding devices on the basis of a three-layer model soil. Methodology. The research was based on comparison of the results of experimental measurements for the existing high voltage energy facilities of Ukraine with the results of the calculation. Results. Comparison showed that the average error decreased from 18 % for the two-layer model to 10 % for the three-layer model. The analysis of the calculated and experimentally determined values of the touch voltage showed a high degree of coincidence. Originality. The adequacy of the calculation procedure of the normalized parameters of the grounding device for model with three-layer soil is substantiated by the results of experimental research on the existing energy objects. Practical value. The obtained results allow us to use calculation procedure to create software to determine with increased accuracy the normalized parameters of grounding device located in three-layer soils.